2019
DOI: 10.1088/1742-6596/1294/6/062089
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Role of Oxidative Stress and Circulating Biochemical markers in Childhood Leukemia

Abstract: Acute lymphoblastic leukemia (ALL) constitutes a family of genetically heterogeneous lymphoid neoplasms derived from B- and T-lymphoid progenitors. The aim of the study was to assess the oxidative status through measurement of antioxidants levels in patients with ALL and deduce any differences in their concentrations from normal values. The study was included 60 children with acute lymphoid leukemia diagnosed by blood film and bone marrow examination and 30 healthy subjects taken as healthy for the initial lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Studies by Almeida MB, et al 13 , Al-Tonbary Y, et al 14 and Pujari KN, et al 15 showed that the MDA level was higher in ALL patients compared to normal subjects. This indicated that the increased lipid peroxides in ALL patients was the result of oxidative stress produced by free radicals 5 . Our study found significantly high MDA levels in both the NAC and placebo groups (p=0.001; 95% CI -0.67 --0.23).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies by Almeida MB, et al 13 , Al-Tonbary Y, et al 14 and Pujari KN, et al 15 showed that the MDA level was higher in ALL patients compared to normal subjects. This indicated that the increased lipid peroxides in ALL patients was the result of oxidative stress produced by free radicals 5 . Our study found significantly high MDA levels in both the NAC and placebo groups (p=0.001; 95% CI -0.67 --0.23).…”
Section: Discussionmentioning
confidence: 97%
“…Many chemotherapeutic agents have been shown to exert their biologic activity through induction of OS in affected cells during cancer therapy 4 . Decomposition of lipid peroxidation product, including malondialdehyde (MDA) is considered as a marker for oxidative stress in the body 5 .…”
Section: Introductionmentioning
confidence: 99%